Obstructive Sleep Apnea and Metabolic Syndrome in Spanish Population - Barreiro, Bienvenido (Bentham Open, 2013)
Obstructive sleep apnea (OSA) is a clinical picture characterized by repeated episodes of obstruction of the upper airway. OSA is associated with cardiovascular risk factors, some of which are components of metabolic syndrome (MS). OBJECTIVES: First, determine the prevalence of MS in patients with OSA visited in sleep clinic. Second, evaluate whether there is an independent association between MS components and the severity of OSA. METHODS: Patients with clinical suspicion of OSA were evaluated by polysomnography. Three groups were defined according to apnea hypoapnea index (AHI): no OSA (AHI <5), mild-moderate (AHI≥ 5 ≤30), and severe (AHI> 30). All patients were determined in fasting blood glucose, total cholesterol, HDL cholesterol, triglycerides and insulin. MS was defined according to criteria of National Cholesterol Education Program (NCEP). RESULTS: A total of 141 patients (mean age 54 ± 11 years) were evaluated. According to AIH, 25 subjects had no OSA and 116 had OSA (41mild-moderate and 75 severe). MS prevalence ranged from 43-81% in OSA group. Also, a significant increase in waist circumference, triglycerides, glucose, blood pressure levels, and a decrease in HDL cholesterol levels was observed in more severe OSA patients. All polysomnographic parameters correlated significantly with metabolic abnormalities. After a multiple regression analysis, abdominal obesity (p <0.02), glucose (p <0.01) and HDL cholesterol (p <0.001) were independently associated with OSA. CONCLUSIONS: Our findings show high prevalence of MS in OSA, especially in severe group. A significant association between OSA and some of the components of MS was found in Spanish population.